The Historical Harpsichord. Four Volumes - Odell, Scott -1935; Leonhardt, Gustav 1928-2012; Goodway, Martha (Stuyvesant, NY Pendragon Press, 1984)
vol. 1: Preface / Gustav Leonhardt -- Introduction / Howard Scott -- Frank Hubbard (1920-1976) / Howard Schott -- Reconstructing the Harpsichord / Frank Hubbard -- THe SUrviving Instruments of the Blanchet Workshop / William Dowd -- In the Direction of the Beginning / Christopher Pagevol. 3: Introduction / Howard Scott -- Bartolomeo Cristofori as Harpsichord Maker / Hubert Henkel -- The Identification and Authentication of Italian String Keyboard Instruments / Denzil Wraightvol. 4: Foreword / Howard Scott -- Harpsichord Decoration - A Conspectus / Sheridan Germann
Includes bibliographical references and index.
Keywords: Ruckers, Hans -- 1533/40-1598 -- the Elder; 17th Century (1601-1700); Harpsichord; Keyboard instrument; Iron; Wire; Europe